2008
DOI: 10.1103/physrevb.77.134509
|View full text |Cite
|
Sign up to set email alerts
|

Explanation of magnetic behavior in Ru-based superconducting ferromagnets

Abstract: We have investigated RuSr 2 Eu 1.5 Ce 0.5 Cu 2 O 10 ͑Ru-1222͒ and RuSr 2 EuCu 2 O 8 ͑Ru-1212͒ samples by using x-ray diffraction, scanning electron microscopy, dc magnetization, ac susceptibility, and resistivity measurements. Based on the results obtained, we propose an explanation of the magnetic behavior of the Ru-based systems. Our model is capable of describing controversial observations of multiple magnetic transitions on temperature dependent dc magnetization measurements as well as the reentrance of ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…I, there were many different interpretations 2,14-16 reviewed in Ref. 4 . In present work, we employ these results in combination with structural magnetic characterisations to derive a consistent magnetic phase diagram with corresponding structural transformations, resolving existing contradictions.…”
Section: Magnetization Measurementsmentioning
confidence: 99%
See 3 more Smart Citations
“…I, there were many different interpretations 2,14-16 reviewed in Ref. 4 . In present work, we employ these results in combination with structural magnetic characterisations to derive a consistent magnetic phase diagram with corresponding structural transformations, resolving existing contradictions.…”
Section: Magnetization Measurementsmentioning
confidence: 99%
“…We note that García et al 22 also observed change in the behaviour of the superconducting region at H = 1 kOe in their field dependent resistivity and ac susceptibility measurements. In the phase diagram, the decreasing T irr (H) and T N (H) curves in increasing field may indicate a metamagnetic transition separating AFM from FM state, likely stipulated by spin exchange interactions described in our phase mixture model 4 and built upon in the following works [10][11][12] . The types of temperature and field dependent magnetic orderings shown in the phase diagram have been determined from the NPD measurements, which will be discussed in detail in Sections A and B.…”
Section: Magnetic Phase Diagrammentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6][7][8] Phase purity, in particular ruling out the presence of magnetic impurities with similar ordering temperature ͓such as SrRuO 3 ͑SRO͔͒, is important in order to support assertions of microscopic uniform coexistence of magnetism and superconductivity. Lattice distortions such as rotations of RuO 6 octahedra can affect the magnetic structure through spin-orbit coupling ͑e.g., Dzyaloshinsky-Moriya interactions 9,10 ͒, antisymmetric exchange interactions, or single-ion anisotropy.…”
mentioning
confidence: 99%